Occurrence of five distinct clades of mermithid nematodes (Nematoda: Mermithidae) infecting black fly larvae (Diptera: Simuliidae) in tropical streams in Malaysia - Emmanuel Yogan Lourdes; Van, Lun Low; Noor Izwan Anas; Mahadimenakbar M. Dawood; Mohd Sofian Azirun; Hiroyuki Takaoka; Zubaidah Ya'cob (Elsevier B.V., 2023)
Mermithids are the most common parasites of black flies and are associated with host feminization and sterilization in infected hosts. However, information on the species / lineage of black fly mermithids in Southeast Asia, including Malaysia requires further elucidation. In this study, mermithids were obtained from black fly larvae collected from 138 freshwater stream sites across East and West Malaysia. A molecular approach based on nuclear-encoded 18S ribosomal RNA (18S rRNA) gene was used to identify the species identity / lineage of 77 nematodes successfully extracted and sequenced from the specimens collected. Maximum likelihood and neighbor-joining phylogenetic analyses demonstrated five distinct mermithid lineages. Four species delimitation analyses: automated simultaneous analysis phylogenetics (ASAP), maximum likelihood Poisson tree processes with Bayesian inferences (bPTP_ML), generalized mixed yule coalescent (GMYC) and single rate Poisson tree processes (PTP) were applied to delimit the species boundaries of mermithid lineages in this data set along with genetic distance analysis. Data analysis supports five distinct lineages or operational taxonomic units for mermithids in the present study, with two requiring further investigation as they may represent intraspecific variation or closely related taxa. One mermithid lineage was similar to that previously observed in Simulium nigrogilvum from Thailand. Co-infection with two mermithids of different lineages was observed in one larva of Simulium trangense. This study represents an important first step towards exploring other aspects of host – parasite interactions in black fly mermithids.